Macroeconomic Determinants of Foreign Direct Investment Inflow in Laos - Leuangliyasak, sitthasay; SOMSAMONE, Vilayphone; DUANGPASITH, Phatsa (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study aims to study macroeconomic determinants of foreign direct investment inflow in Lao PDR, which includes macroeconomic variables such as gross domestic product growth rate (GDPGRO), government investment spending (GI), exchange rate (EXR), inflation rate (IFR), interest rate (IR), openness trade (OPTR) and money supply (MS) from 2001-2022. This results found that: The foreign direct investment inflow has 12,298.57 million US dollars on an average per year is equal to 559.03 million US dollars and has an average growth rate of 4.73% per year, for the public expenditure used to investment is increasing every year with an average growth rate of 10.96% per year. The exchange rate of kip per US dollar has an increasing trend but overall there is a growth rate equal to 1 digit only in 2022 there is a growth rate equal to 2 digits which is equal to 45.94%. For the inflation, the growth rate is 6.33% per year, which is the year with the lowest inflation rate is 2017 which is equal to 0.83% and the year with the highest inflation rate is 2022 which is equal to 22.96%, The decreasing trend in which the year with the highest interest rate on US currency loans is 2002 which is equal to 13.5% and the year with the lowest interest rate on US currency loans is 2011 which is equal to 8.15%, the open trade has an increasing trend. The year with the highest increase in 2021 is equal to 77.91% of GDP and the money supply is increasing every year. For the analysis of macroeconomic factors to foreign direct investment, it was found that the economic growth rate of gross domestic product (GDPGRO), public investment expenditure, the exchange rate of kip per US dollar and the money supply have a positive coefficient and reject the null hypothesis with a statistical significance level of 0.01 and 0.05 indicates that it is a doubtful factor for foreign direct investment to increase. Meanwhile, the inflation rate has a negative coefficient and rejects the null hypothesis at a statistical significance level of 0.05, which is a factor that reduces foreign direct investment transfers. For the interest rate in dollars and the open trade, there are accepted null hypothesis, it shows that there is no effect on the transfer of foreign direct investment.